A challenging case of pelvic inflammatory disease due to miliary tuberculosis. Issue 3 (29th August 2018) - Damanti, Sarah; Clerici, Marta; Bonini, Giulia; Duiella, Silvia F.; Cesari, Matteo
Abstract : A woman presented with symptoms of salpingitis 7 months after delivery. Initially treated as pelvic inflammatory disease, the condition was revealed to be genital localization of miliary tuberculosis.